The Effect Of Receivable Turnover And Inventory Turnover On Profit Margin In Pt. Nippon Indosari Corpindo, Tbk - Ima Andriyani; Ulil Amri; Firdaus Sianipar; Rusmida JH Hutabarat (Best Journal of Administration and Management, 2024)
The purpose of this research is to determine the effect of Receivable Turn Over and Inventory Turn Over on Profit Margin of PT. Nippon Indosari Corpindo, Tbk. The variables used in this research are Receivable Turn Over and Inventory Turn Over, Profit Margin. The population in this research is financial reports for a period of five years in the form of quarterly data. The type of research used is quantitative. The research techniques used are multiple linear regression, hypothesis testing, F test and t test. The regression results to obtain Profit Margin are influenced by Receivable Turn Over and Inventory Turn Over. The results of the hypothesis test, namely the F test, showed that there was a simultaneous influence of Receivable Turn Over and Inventory Turn Over on Profit Margin, while the t test results of the Receivable Turn Over variable partially had a significant influence on Profit Margin as well as the Inventory Turn Over variable partially having an influence on Profit Margins.